Magnetization Reversal and Thermal Switching in Randomly Oriented L10 Thin Films - Alqarni, Ahlam (My University, 2018)
Equiatomic FePt has been identified as the promising candidate for the next generation Heat Assisted Magnetic Recording (HAMR). HAMR is a new hard disk drive (HDD) technology, which requires highly anisotropic magnetic media, where the anisotropy energy (Ku ~108 erg/cm3) is large enough to sustain thermally stable small grains ultimately down to ∼ 3 - 4 nm. Static magnetism and thermally activated magnetic relaxation were investigated in granular FePt films (20 nm-200 nm thick) with random magnetic anisotropy through hysteresis loop, torque curve and magnetization time dependence measurements. While the magnetism of thicker film (200 nm thick) is dominated by a single switching of the ordered L10 phase, thinner film (20 nm) displays a double switching, which is indicative of the presence of the disordered cubic phase. The pronounced behavior of double switching in thinner film suggests that the film grain boundary is composed of soft cubic magnetic phase. The magnetic relaxation study reveals that magnetic viscosity S of the films is strongly dependent on the external applied field and exhibits a maximum value (12 kAm) around the switching field and a vanishing behavior at low (1 kOe) and large (12 kOe) fields.
Keywords: Magnetic materials; Nanoscience; Materials science